2012
DOI: 10.1016/j.sapharm.2010.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perspectives of the Australian Home Medicines Review Program: Benefits and barriers

Abstract: BACKGROUND: The Australian Home Medicines Review (HMR) is a free consumer service to assist individuals living at home to maximize the benefits of their medicine regimen and prevent medication related problems. It consists of a pharmacist reviewing a person's medicines and collaborating with the general practitioner to optimize the individual's medicine management. The uptake of this service has remained below the projected use although the program has been shown to successfully identify medication related pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
72
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 18 publications
8
72
0
1
Order By: Relevance
“…The respondents in this study, similar to other HMR studies with non-Indigenous Australians [26,27] indicated that two significant barriers to HMR program uptake were lack of awareness of the program by health professionals and lack of GP referrals. Studies have also found that some GPs often do not value the role of pharmacists in performing medication management review [16,17].…”
Section: Discussionsupporting
confidence: 82%
“…The respondents in this study, similar to other HMR studies with non-Indigenous Australians [26,27] indicated that two significant barriers to HMR program uptake were lack of awareness of the program by health professionals and lack of GP referrals. Studies have also found that some GPs often do not value the role of pharmacists in performing medication management review [16,17].…”
Section: Discussionsupporting
confidence: 82%
“…12 There has also been research into perceived barriers to implementing CMRs, 13,14 and initiatives to promote greater uptake among those at high risk of ADEs. 15 While the development and implementation of CMR has continued to be the subject of research, there has been no previous systematic review of Australian CMR research.…”
Section: Introductionmentioning
confidence: 99%
“…For example, from a patient's perspective as a key stakeholder, HMRs improved their knowledge, skills and confidence in using medicines. [5][6][7] Patients also reported a high satisfaction rate with the service. [5][6][7] From a GP's perspective, these doctors alone have complete control over the HMR and RMMR program activities: pharmacists can only initiate an HMR or RMMR in response to a GP's referral.…”
mentioning
confidence: 99%
“…[5][6][7] Patients also reported a high satisfaction rate with the service. [5][6][7] From a GP's perspective, these doctors alone have complete control over the HMR and RMMR program activities: pharmacists can only initiate an HMR or RMMR in response to a GP's referral. Given that these referrals have been made, 10 it would appear obvious that there is support from this sector.…”
mentioning
confidence: 99%
See 1 more Smart Citation